Crime prevention of unaccompanied foreign minors in street situation - Casado Patricio, Elena (My University, 2023)
The research question is what role institutional legitimacy or confidence plays in the prevention of criminological risk situations of unaccompanied foreign minors in street situations. Institutional legitimacy is related to regulatory conformity, and this could imply a criminological prevention strategy for these minors. The above, together with the considerable number of unaccompanied foreign minors in street situations and the lack of studies that try to know the trust they have in the institutions in charge of their protection, makes the work presented here especially important. To respond to the previously stated objectives, a methodological triangulation has been carried out through structured questionnaires and the systematization of the information collected thanks to participant observation, in field diaries and individual diagnosis sheets. The results show that confidence in institutions is low at a general level, but that it varies depending on the police force and the protection center asked about. In addition, other variables such as direct experiences can influence the perception of institutional legitimacy of minors and confirm that confidence or legitimacy is related to the degree of obedience and conformity.
Keywords: Derecho Público; Migrantes-Legislación; Menores de edad; Minors; Legitimacy; Crime; Prevention